Converting from seepage irrigation to plasticulture for vegetable production: A case study - Charles E. Barrett; Lincoln Zotarelli; Brian S. Taylor; Lucas G. Paranhos; Mark Warren (EDIS)
Cabbage production in Florida has been dominated by the use of seepage or sub-irrigation, because it is inexpensive to maintain and simple to use, but it can require vast quantities of water to be pumped from the aquifer in low rainfall years. Plasticulture has been proposed as an alternative production method for cabbage production in Florida. An on-farm demonstration was setup on Greene’s Farms in Bunnell, FL to provide a platform for collaboration between researchers, growers and extension professionals. This 6-page fact sheet illustrates an innovative approach converting from seepage irrigation to plasticulture and points out some options and challenges for growers considering a plasticulture system. Written by Charles E. Barrett, Lincoln Zotarelli, Brian S. Taylor, Lucas G. Paranhos, and Mark Warren, and published by the UF Department of Horticultural Sciences, July 2014.